2017
DOI: 10.1371/journal.pntd.0005313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and functional triatomine genomics reveals reductions and expansions in insecticide resistance-related gene families

Abstract: BackgroundTriatomine insects are vectors of Trypanosoma cruzi, a protozoan parasite that is the causative agent of Chagas’ disease. This is a neglected disease affecting approximately 8 million people in Latin America. The existence of diverse pyrethroid resistant populations of at least two species demonstrates the potential of triatomines to develop high levels of insecticide resistance. Therefore, the incorporation of strategies for resistance management is a main concern for vector control programs. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 73 publications
2
60
0
6
Order By: Relevance
“…These data suggest that other mechanisms could be involved in triatomine insecticide resistance. Traverso et al (2017) analyzed the main enzyme superfamilies known to be involved in metabolic insecticide resistance in four important Chagas disease vector species (GST, CYP and CCE). They found that the CYP4 gene analyzed was significantly overexpressed in resistant individuals to pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that other mechanisms could be involved in triatomine insecticide resistance. Traverso et al (2017) analyzed the main enzyme superfamilies known to be involved in metabolic insecticide resistance in four important Chagas disease vector species (GST, CYP and CCE). They found that the CYP4 gene analyzed was significantly overexpressed in resistant individuals to pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, triatomine insecticide resistance is a complex and plastic trait as it involves different mechanisms (González Audino, Vassena, Barrios, Zerba, & Picollo, ; Mougabure‐Cueto & Picollo, ; Roca‐Acevedo, Picollo, Capriotti, Sierra, & Santo‐Orihuela, ) with a polygenic determinism (Pessoa et al., ). This trait shall now be investigated through functional genomics approaches (as genuinely initiated by Traverso et al., ), if one is to uncover the true nature of its variations, and propose some mechanistic explanations to the intriguing associations of the highest level of resistance with a specific genetic background and environmental variables (Bustamante Gomez et al., ).…”
Section: Triatomine Life‐history Evolution and Vector Control Challengesmentioning
confidence: 99%
“…Target site modification (alteration as a result of amino acid substitution or mutation) is one mechanism of insecticide resistance in insects and has been reported in both agricultural pests and insect vectors of medical importance (Marcombe et al ., ; Du et al ., ; Ribeiro et al ., ; Sindhu et al ., ). Metabolic resistance to insecticides is another common mechanism, whereby elevated activities of detoxification enzymes such as cytochrome P450s, monooxygenases, carboxylesterases and/or glutathione S‐transferases (GSTs) break down insecticides (Baek et al ., ; Sonoda, ; You et al ., ; Traverso et al ., ).…”
Section: Introductionmentioning
confidence: 97%